2006
DOI: 10.1021/ol062688b
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Acetate Aldol Additions Using Mesityl-Substituted Chiral Auxiliaries

Abstract: [reaction: see text] Highly diastereoselective acetate aldol additions using chlorotitanium enolates of mesityl-substituted N-acetyloxazolidinethione and N-acetylthiazolidinethione auxiliaries are reported. These additions proceed in high yields and diastereoselectivities (93:7 to 98:2) for aliphatic, aromatic, and ,-unsaturated aldehydes. Double diastereoselective acetate aldol additions are also reported and are found to proceed in high yields and diastereoselectivities (90:10 to 97:3).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(52 citation statements)
references
References 30 publications
1
50
0
Order By: Relevance
“…A subsequent report from the Evans lab demonstrated that ''Evans'' syn-aldol adducts (10) (Scheme 7.7) are also obtained through the chlorotitanium enolates using titanium tetrachloride as the Lewis acid and diisopropylethylamine or TMEDA as the base [4]. Concurrently, Thornton reported the selective formation of the ''non-Evans'' syn-diastereomer (12) Evans model, was proposed to explain the dominant formation of the ''non-Evans'' syn-isomer [18]. The chlorotitanium enolates offer some potential benefits.…”
Section: Propionate Aldol Additionsmentioning
confidence: 98%
See 2 more Smart Citations
“…A subsequent report from the Evans lab demonstrated that ''Evans'' syn-aldol adducts (10) (Scheme 7.7) are also obtained through the chlorotitanium enolates using titanium tetrachloride as the Lewis acid and diisopropylethylamine or TMEDA as the base [4]. Concurrently, Thornton reported the selective formation of the ''non-Evans'' syn-diastereomer (12) Evans model, was proposed to explain the dominant formation of the ''non-Evans'' syn-isomer [18]. The chlorotitanium enolates offer some potential benefits.…”
Section: Propionate Aldol Additionsmentioning
confidence: 98%
“…Thiazolidinethiones can also be prepared by exposure of the amino alcohol to sulfuric acid followed by treatment with potassium O-ethyl xanthate and aqueous base [11] or by exposure of the β-chloro amine salt to carbon disulfide and aqueous base (Scheme 7.4) [12].…”
Section: Preparation Of Oxazolidinethione and Thiazolidinethione Chirmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the case of thiazolidinethione (196) Evans oxazolidinone auxiliary fails to give high selectivities in acetate aldol reactions, Sammakia speculated that the boron-mediated reaction from 196 ((3) in Scheme 1.67) proceeded through an open transition state, but a more common cyclic chairlike transition state was not ruled out (XLII and XLIII, respectively, in Scheme 1.69) [159a]. On the other hand, the opposite stereochemistry obtained in the titanium-mediated reactions led Phillips [157a] and Crimmins [158] to propose a chelated chairlike or a non-chelated boatlike transition states (XLIV and XLV, respectively, in Scheme 1.69) to account for the observed stereocontrol.…”
Section: Metal Enolates 45mentioning
confidence: 99%
“…[158] reported that N-acetyl oxazolidinethiones (192) and (193) underwent highly diastereoselective additions to aliphatic, α, β-unsaturated, and aromatic aldehydes, affording aldols (194) and (195) in high yields and diastereoselectivities ((1) and (2) in Scheme 1.67), whereas Sammakia [159], Crimmins [158,160], and Olivo [161] described that boron and titanium enolates from N-acetyl thiazolidinethiones (196)(197)(198) provided high levels of stereocontrol with a wide range of aldehydes, affording aldols (199)(200)(201) in high yields ( (3)(4)(5) in Scheme 1.67) [162]. This chemistry has been widely applied to the synthesis of natural products [163], as can be illustrated by two concurrent reports on the total synthesis of cyanolide A (202).…”
mentioning
confidence: 99%